Not fair at all: Working conditions on online platforms for language services - Patrick Feuerstein; Tatiana López; Giulia Varaschin; Mark Graham (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2023)
It's hard to imagine working life without the language services provided by digital platforms. However, it raises the question: How fair are the working conditions for employees engaged with these platforms? To shed light on this matter, a team of researchers from the Fairwork project conducted an in-depth examination of nine platforms, assessing them based on five principles of fair work.
Keywords: 300